2011
DOI: 10.1016/j.neuron.2011.02.021
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Role for Neurofascin in Regulating Action Potential Initiation through Maintenance of the Axon Initial Segment

Abstract: SummaryThe axon initial segment (AIS) is critical for the initiation and propagation of action potentials. Assembly of the AIS requires interactions between scaffolding molecules and voltage-gated sodium channels, but the molecular mechanisms that stabilize the AIS are poorly understood. The neuronal isoform of Neurofascin, Nfasc186, clusters voltage-gated sodium channels at nodes of Ranvier in myelinated nerves: here, we investigate its role in AIS assembly and stabilization. Inactivation of the Nfasc gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
193
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(204 citation statements)
references
References 66 publications
10
193
0
1
Order By: Relevance
“…Loss of this important upstream anchor caused loss of neuronal polarity, a transition from axonal to dendritic identity and the formation of dendritic spines on the former axon (Hedstrom et al, 2008;Sobotzik et al, 2009). Additionally, recent evidence suggests that the cell-adhesion molecule Neurofascin186 is involved in the stabilization of the axon initial segment (Zonta et al, 2011). Finally, it has also been shown that the expression of a constitutively-active IKK increases spine density in neurons (Russo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of this important upstream anchor caused loss of neuronal polarity, a transition from axonal to dendritic identity and the formation of dendritic spines on the former axon (Hedstrom et al, 2008;Sobotzik et al, 2009). Additionally, recent evidence suggests that the cell-adhesion molecule Neurofascin186 is involved in the stabilization of the axon initial segment (Zonta et al, 2011). Finally, it has also been shown that the expression of a constitutively-active IKK increases spine density in neurons (Russo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we aimed to validate a PRM-MS assay consisting of a panel of proteins presumed to be involved in processes regarding secretory vesicle functioning, synaptic functioning, and innate immunity [12][13][14][15][16][17][18][19][20][21]. Having performed a pilot study [29], in the present study, we investigated this panel in a larger and independent cohort that included subjects with MCI in addition to patients with AD dementia and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a decreased level in brain tissue and CSF of patients with AD compared with control subjects has also been described [27,28,40]. Studies on the role of NRXNs, NPTX1, NFASC, and NCANP in AD are rare, although the proteins have all been suggested to have a role in synapse formation, plasticity, and stability [17][18][19][20][21]. On the basis of using MS-based proteomics, CSF NRXN-1 has been found to be slightly decreased in patients with AD compared with control subjects in a small cohort of 16 subjects [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF186 is dispensable for the assembly of AIS and nodes Zonta et al 2008;Feinberg et al 2010), but is critical for the maintenance of the AIS (Zonta et al 2011), as well as of nodes in the PNS ) and the CNS (Desmazieres et al 2014). Interestingly, CNS nodes are more susceptible to disruption after genetic deletion of NF186 in adult mice than PNS nodes, an observation that likely reflects the major contribution of the PNJ in the CNS.…”
Section: Maintaining Excitable Domains In Myelinated Axonsmentioning
confidence: 98%